Formulation and Characterization of Dewandaru Fruit Extract in Nanocarrier System - Melati Septiyanti; Nurfauziyah; Marissa Angelina; Rizna Triana Dewi; Sofa Fajriah; Yenny Meliana (BRIN Publishing (Penerbit BRIN), 2024)
Dewandaru (Eugenia uniflora L.) is a herbaceous plant that grows in tropical and subtropical regions. The fruit extract can prevent oxidative damage and cholinergic changes. It contributes to antihyperglycemic, antihyperlipidemic, and neuroprotective due to its antioxidants and antidepressant effect. It also possesses antibacterial and anti-inflammatory activity and potentially prevents cardiovascular disease and cancer. In this study, dewandaru fruit extract was formulated in the nanocarrier system (nanoemulsion and nanoencapsulation) to preserve product stability and improve product dispersibility and bioavailability. The nanoemulsion optimum formulation condition was obtained on dewandaru fruit extract concentration 10 wt%, oil/surfactant ratio 0.25, and homogenization speed 20.000 rpm, resulting in particle size of 46.4 ± 0.4 nm and polydispersity index 0.480 ± 0.015. The optimum nanoemulsion formulation was further processed to nanoencapsulation along with milling to produce finer particles. The nanoencapsulation milled for 120 minutes produced encapsulation powder with a size of 5.8 ± 3.340 μm. Accordingly, the nanocarrier technology for dewandaru fruit extract promoted a versatile medicinal preparation both in liquid and solid form. However, the size reduction by milling might disrupt the efficiency of the encapsulation release system. Without the proper coating, as orally administrated, the compound rapidly dissolved before it reached the targeted site.